Modular MLV-VLPs co-displaying ovalbumin peptides and GM-CSF effectively induce expansion of CD11b+ APC and antigen-specific T cell responses in vitro. (September 2018) - Gogesch, Patricia; Schülke, Stefan; Scheurer, Stephan; Mühlebach, Michael D.; Waibler, Zoe
Graphical abstract: Highlights: VLPs can be used as modular vaccines co-displaying antigen (OVA) and adjuvant (GM-CSF). GM-CSF displayed on VLPs mediates expansion and proliferation of CD11b + cells. Compared to a non-modular mixture, modular VLPs increase specific T cell responses. Abstract: The development of novel vaccination strategies is a persistent challenge to provide effective prophylactic treatments to encounter viral infections. In general, the physical conjugation of selected vaccine components, e.g. antigen and adjuvant, has been shown to enhance the immunogenicity and hence, can increase effectiveness of the vaccine. In our proof-of-concept study, we generated non-infectious, replication deficient Murine Leukemia Virus (MLV)-derived virus-like particles (VLPs) that physically link antigen and adjuvant in a modular fashion by co-displaying them on their surface. For this purpose, we selected the immunodominant peptides of the model antigen ovalbumin (OVA) and the cytokine granulocyte macrophage-colony stimulating factor (GM-CSF) as non-classical adjuvant. Our results show that murine GM-CSF displayed on MLV-VLPs mediates expansion and proliferation of CD11b + cells within murine bone marrow and total spleen cells. Moreover, we show increased immunogenicity of modular VLPs co-displaying OVA peptides and GM-CSF by their elevated capacity to induce OVA-specific T cell-activation and -proliferation within OT-I and OT-II splenocyte cultures. These enhanced effects were not achieved by using an equimolar mixture of VLPs displaying either OVA or GM-CSF. Taken together, OVA and GM-CSF co-displaying MLV-VLPs are able to target and expand antigen presenting cells which in turn results in enhanced antigen-specific T cell activation and proliferation in vitro . These data suggest MLV-VLPs to be an attractive platform to flexibly combine antigen and adjuvant for novel modular vaccination approaches.